The use of cohesive devices in high proficiency and low proficiency ESL argumentative essays : a comparative study - Siti 'Aishatul-Humairah bt Muhammad Fisol (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2015)
Using Halliday and Matthiessen's (2004) taxonomy of cohesive devices for analysis, this study investigates the use of cohesive devices in 100 argumentative compositions produced by ESL university students at two different levels of proficiency. Given the importance of cohesion in writing, this study also investigates the correlation between the use of cohesive devices and writing scores. Data were quantified and analysed by computing all occurrences of cohesive devices using the IBM SPSS software (22.0). Descriptive statistics, Independent sample t-test, correlation coefficient and qualitative analysis were performed in order to answer the research questions. The findings reveal that the students were able to use varieties of cohesive devices in their argumentative writing. Reference was found to be the most frequent category employed by students regardless of proficiency followed by lexical category of repetition. There was significant difference in the total use of cohesive devices between high and low proficiency essays. The writing scores also reveal significant correlation in the total use of cohesive devices despite several errors identified in the writings. The results of this study are expected to lead to a better understanding of the role of learning and teaching cohesion in writing in the ESL contexts.